Smart–Green Tourism: The Role of Digital Technologies in Strengthening Sustainable Practices at Destination Bali - SUDARMINI, Ni Made; DAMAYANTI, Ida Ayu Kade Werdika; MULIATI, Ni Kadek; DEWI, Putu Esa Naranata (Journal of Tourism Economics and Policy, 2026)
This study explores how digital technologies are utilized to promote and implement sustainable tourism practices in Bali, Indonesia. Using a qualitative descriptive approach, the research investigates the integration of smart systems—such as e-ticketing, digital waste management applications, and eco-friendly mobile platforms—in shaping sustainable tourism behavior and governance. Data were collected through in-depth interviews, participant observation, and document analysis conducted in two key destinations: Sanur, representing government-led smart city initiatives, and Ubud, representing community-based green tourism. The findings reveal that digital innovation enhances efficiency, transparency, and environmental accountability while also fostering tourists’ awareness and participation in sustainability practices. Social media engagement, particularly through digital storytelling and user-generated content, plays a significant role in strengthening Bali’s image as a smart and sustainable destination. The study proposes a conceptual model of Smart–Green Tourism comprising four components: digital infrastructure, digital engagement, collaborative governance, and continuous monitoring. This model demonstrates how technological innovation and local cultural values can work synergistically to promote environmental stewardship and destination resilience. The study concludes that successful implementation of smart–green tourism in Bali requires cross-sector collaboration, inclusive digital literacy, and sustained commitment to eco-conscious innovation.